Integrating Pencak Silat Values into Character Education in Elementary Schools: An Ethnopedagogical Study at Pusaka Arya Kemuning Cirebon - Nurhidayat, Wafi; Uswatun Hasanah,; Iin Wariin Basyari,; Rahmad Khodari, (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the character values contained in the martial art of pencak silat and explain how these values can be integrated into character education in elementary schools. The research method used is qualitative with a descriptive approach, employing data collection techniques such as documentary study, participatory observation, and in-depth interviews conducted at the Pencak Silat Paksi PPS Academy, located in Cirebon City, West Java. Three informants involved in the program were selected through purposive sampling, namely a pencak silat instructor, a student, and an elementary school teacher. Data analysis was conducted thematically based on cultural theory, encompassing the dimensions of ideas (mentifact), actions (sociofact), and artifacts. The research findings indicate that pencak silat is not only a martial art but also a means of character development rooted in local wisdom and religious values such as honesty, responsibility, discipline, self-control, patience, and a spirit of cooperation. These values are instilled in students through structured training methods, cultural symbols, and spiritual exercises. It is hoped that the integration of pencak silat values into character education in elementary schools can promote holistic and contextual character development in students that aligns with national culture. This research contributes to the development of a locally-based character education model to strengthen students' identity and moral foundation at the national and international levels.